THE INTRODUCTION OF SURDOPEDAGOGY INTO UZBEKISTAN’S HIGHER EDUCATION SYSTEM AND THE INDIVIDUALS WHO LED THIS PROCESS - Abdullayeva Nargiza O‘ktamovna (Web of Journals Publishing, 2025)
This teaching-methodical manual is written for teachers of the special education system, as well as teachers of general education schools where inclusive education has been introduced, who address the educational challenges of deaf and hard-of-hearing children. It thoroughly describes Uzbek sign language and the system for teaching it.
Keywords: Sound-based language, deaf-mute women of some Caucasian peoples tabooed from speaking with sounds, World Federation of the Deaf